Development of alginate dialdehyde-gelatin based bioink with methylcellulose for improving printability - Reakasame, Supachai; Dranseikiene, Dalia; Schrüfer, Stefan; Zheng, Kai; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering C, 2021)
This study used methylcellulose (MC) to improve the printability of the alginate dialdehyde-gelatin (ADA-GEL) based bioink. The printability as well as the capability to maintain shape fidelity of ADA-GEL could be enhanced by the addition of 9% (w/v) MC. Moreover, the properties of the ink crosslinked with Ca2+ and Ba2+ were investigated. The samples crosslinked with Ba2+ were more stable and stiffer than the Ca2+ crosslinked samples. However, both Ca2+ and Ba2+ crosslinked samples exhibited a similar trend of MC release during incubation under cell culture conditions. The toxicity test indicated that both samples (crosslinked with Ca2+ and Ba2+) exhibited no toxic potential. The fabrication of cell-laden constructs using the developed bioinks was evaluated. The viability of ST2 cells in Ba2+ crosslinked samples increased while for Ca2+ crosslinked samples, a decreased viability was observed over the incubation time. After 21 days, cell spreading in the hydrogels crosslinked with Ba2+ occurred. However, a certain degree of cell damage was observed after incorporating the cells in the high viscosity bioink.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Alginate; Alginate dialdehyde; Biofabrication; Bioinks; Methylcellulose